SOCIAL SOLIDARITY BETWEEN HINDU STUDENTS AT TADULAKO UNIVERSITY - Made Agus Adi Putra; Agus Budi Wirawan; I Wayan Mudita (STAH Dharma Sentana Sulawesi Tengah, 2020)
Hindu students should have mutual respect and respect for each other. This research is to get a direct and general description of the results of research on Hindu students at Tadulako University, the problem that occurs is a form of student social solidarity as well as supporting and inhibiting factors. a very important role in improving the quality and quality and progress of a nation. Thus, students are expected to have good intellectuals and noble character. To gain knowledge and in order to have a high intellectual level, students cannot walk alone. Students need friends who can be invited to work together in their education. By frequently working together, students become more familiar with each other, thus creating a strong bond between each other and causing a sense of solidarity between students.